PEMANFAATAN SUMBER DIGITAL DALAM LITERASI MEMBACA MAHASISWA: STUDI KASUS DI PROGRAM STUDI PENDIDIKAN BAHASA DAN SATRA INDONESIA UNIVERSITAS EKASAKTI PADANG - Khairani, Zuraida; Chan, Dwi Mutia; Hayati, Najmi (STKIP Pesisir Selatan, 2025)
This study aims to analyze the use of digital sources in improving reading literacy of students of the Indonesian Language and Literature Education Study Program, Ekasakti University, Padang. The development of information technology provides easy access to various digital reading sources such as e-books, online journals, online scientific articles, educational blogs, and other digital media. The research method uses a qualitative approach with a case study design, involving 30 2nd semester students as informants. Data were collected through interviews, observations, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that the use of digital sources has a positive impact on increasing reading interest, critical thinking skills, and active involvement of students in learning. However, challenges were also found such as lack of skills in evaluating the credibility of information and the risk of plagiarism. The role of lecturers as facilitators is very important in guiding students to use digital sources effectively and responsibly. With an adaptive learning strategy, the use of digital sources can strengthen reading literacy that is relevant to the demands of 21st century education.